Catheter ablation of atriofascicular Mahaim fibers guided by the activation potential - Silva,Márcio Augusto (2003)
OBJECTIVE: To determine whether recording of the activation potential may be used as an isolated criterion to guide catheter ablation of atriofascicular Mahaim fibers. METHODS: We studied 6 patients (5 females, mean age of 26±7.3 years) with paroxysmal tachycardias with a wide QRS complex, whose electrophysiological study diagnosed atriofascicular Mahaim fibers. Mapping and catheter ablation were performed in sinus rhythm, guided only by the recording of the activation potential of the fiber. RESULTS: Efficacy in ablation was achieved in all patients. The fibers were located in the right lateral region of the tricuspid ring in 3 patients, right posterolateral region in 2, and right anterolateral region in 1. A mean of 5.3±3 radiofrequency applications was performed. The mean fluoroscopy time was 46.6±25 minutes, and the mean duration of the procedure was 178.6±108 minutes. No complication occurred. In a mean 20-month follow-up, all patients were asymptomatic and receiving no antiarrhythmic drugs. CONCLUSION: Catheter ablation of Mahaim fibers may be performed with good safety and efficacy by mapping the activation potential of the tricuspid ring in sinus rhythm.